1972
DOI: 10.1002/kin.550040202
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of alkyl radical reactions by kinetic spectroscopy. II. Combination of the methyl radical with the oxygen molecule

Abstract: The kinetics of the reaction CH3 + 0 2 (+M) -+ CH302 (+MI have been studied, using the technique of flash photolysis and kinetic spectroscopy to follow the methyl radical concentration. The order of the reaction lies between 2 and 3 throughout the range of pressure from 25 to 380 torr at 22"C, and the results are consistent with a single reaction sequence:The limiting values of the third-order rate coefficients at low pressures are (3.6 f 0.3) X 10" 1. mole-2 sec-' when M is neopentane, and (0.94 f 0.03) X 10"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1972
1972
1987
1987

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 38 publications
(46 reference statements)
1
28
0
Order By: Relevance
“…For reactions between 0 atoms and CH3 two separate radical sources were required. CH3 radicals were produced by reaction (5), (5) F + CH4 + CH3 + HF The F atoms required were generated by passing 1% CF4 in He through a microwave discharge D1 located in a 1-cm inner diameter &03 sidearm, 20-30 cm upstream from the entry point to the main flow tube. Gas emerging from D1 was diluted -1000-fold by the main helium flow, which entered the gas stream -10 cm downstream from D1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For reactions between 0 atoms and CH3 two separate radical sources were required. CH3 radicals were produced by reaction (5), (5) F + CH4 + CH3 + HF The F atoms required were generated by passing 1% CF4 in He through a microwave discharge D1 located in a 1-cm inner diameter &03 sidearm, 20-30 cm upstream from the entry point to the main flow tube. Gas emerging from D1 was diluted -1000-fold by the main helium flow, which entered the gas stream -10 cm downstream from D1.…”
Section: Methodsmentioning
confidence: 99%
“…Basco et al [5] concluded that it was possible to eliminate any plausible two-body reaction such as (41, (…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate constant for reaction (3b) has not been measured. However, the rate constant for the corresponding reaction of the methyl radical was estimated to be not much greater than 2 X lo5 liter mole-lsec-l by Basco, James, and James in 1972 [3]. A low value was confirmed both by the results of very low pressure pyrolysis studies in 1973 [lo], and by the extrapolation of an Arrhenius expression fitted to the results of eight studies of the shock-initiated oxidation of methane in a recent review [ l l ] .…”
Section: Evaluation Of K 4 F / C (X)mentioning
confidence: 99%
“…These values and the fact that E2 should be low were used as a starting point for a computer fit of the experimental data with the above reaction scheme. The rate constant k 1 was taken from [28], k5 from [29], and k.3, k4 were estimated as described above. The following expressions for k ; and k2 were obtained: may be significant contributions from vibrationally excited states in hb since the reaction is endo-ergic and vibrational energy may effectively assist in surmounting the barrier.…”
Section: Ch4-fz-ar Systemmentioning
confidence: 99%